PENGARUH INVESTASI ASET TETAP DAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 S.D 2017 - Nopitasari Pitri; Makhdalena Makhdalena; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the influence of fixed asset investment and working capital on profitability both of simultaneously and partially at manufacturing companies of automotive and components sub sector which is listing in the Indonesia Stock Exchange for 2013 until 2017. The population of this study is all of the companies of automotive sector and components which is listing in the Indonesia Stock Exchange for 2013 until 2017 which data was examined by census. This study used secondary data sourced from annual report. The data analysis technique used multiple linier regression with the help of the program called SPSS (Statistical Package for Social Science). The result of this study showed that fixed asset investment and working capital simultaneously had an influence on profitability. Fixed asset investment partially had a negative influence on profitability. While working capital had a positive influence on profitability.Key Words: Fixed Asset Investment, Working Capital, and Profitability